Relationship Between Assertiveness Level with Emotional Labor Behavior of Nursing Students - Banu Tufan Koçak; Nihal Ünaldı Türkkan; Rujnan Tuna (Sağlık ve Hemşirelik Yönetimi Dergisi, 2015)
OBJECTIVE: Research was planned descriptive and correlational design in order to determine the relatonship between assertiveness level with emotional labor behavior of nursing students. METHODS: In the study, without going into any sample selection all the students who are enrolled to the nursing faculty at a public university and willing to participate in the study were included (921 students). 10 questions to determine the characteristics of the students, "Emotional Labor Behavior Scale" and "Rathus Assertiveness Inventory"(RAI) have been used for collection of the data. Data evaluated by using percentage, average and Pearson correlation analysis. RESULTS: It has been found that 44.7% of students were assertive, "Emotional Labor Behavior Scale" total point average of the students was 3.75+-0.78, and between total mean scores RAI and "Emotional Labor Behavior Scale" was very weak negative relationship that was found to be nonsignificant (p>0.05) CONCLUSION: There was not relationship between assertiveness level and emotional labor behavior of nursing students.